Analisis Peran Guru dan Orang Tua dalam Kebijakan Kawasan Tanpa Rokok di MA SMIP 1946 Banjarmasin - Siti Shofaa Lawahizoh; Yeni Riza; Ridha Hayati; Fakhsiannor Fakhsiannor (Universitas Respati Indonesia, 2025)
The Smoke-Free Area (SFA) policy in schools should be the first line of defense in protecting adolescents from the dangers of smoking. However, in environments with a strong smoking culture, this policy often faces obstacles, one of which is low participation from teachers and parents. This study was conducted to analyze the role of teachers and parents in the implementation of the The Smoke-Free Area policy at MA SMIP 1946 Banjarmasin. This study was a descriptive qualitative study using snowball sampling techniques. Data were collected through interviews, observations, and documentation ang analyzed using the Miles-Huberman analysis technique. Data validity was tested using technical triangulation. The results of this research were obtained from 9 informants consisting of the principal, 4 teachers and 4 parents who showed that teachers have actively enforced the SFA through supervision, raids, sanctions, awarding points for violations and summoning parents. Conversely, parental involvement is still lowl, where permissive attitudes normalize smoking behavior. Using family ecological theory, it can be concluded that this study emphasizes that the succes of SFA in schools is not sufficient only with enforcement at the school level, but also requires active collaboration from parents to counter pro-smoking cultural norms at home.